Single-function approach to calibrating whatman no. 42 filter paper based on suction versus water content relationships - Bicalho, Katia (2015)
Several suction–water-content (s-w) calibrations for the filter paper method (FPM) used for soil-suction measurement have been published. Most of the calibrations involve a bilinear function (i.e., two different equations) with an inflection point occurring at 60 kPa<s<100 kPa (i.e., 40 %<w<50 %). An approach for defining a continuous calibration function with a smooth transition between the high and low suctions based on a regression analysis of various previously published calibrations obtained for filter paper Whatman No. 42 (W42) is presented and discussed. The approach is applied herein to data obtained from three establish bilinear calibrations (six equations) for W42 filter paper to determine the two fitting parameters of the continuous function. An experimental evaluation of the new calibration show that the suctions estimated by the contact FPM test using the proposed function compare well with suctions measured by other laboratory techniques for two different soils for the suction range of 50 kPa<s<400 kPa, which corresponds to a water content range of 30 %<w<55 %.